Actividades de autocuidado en pacientes diabéticos tipo 2 que acuden al Centro de Salud Hugo Guillermo González - Tene Conde, Ximena Maribel (2022)
Self-care is the ability of people to promote health and prevent disease, maintain good health and cope with illness and disability with or without the support of a health professional; this is why this research was carried out to determine self-care activities in patients with type 2 diabetes who come to the Hugo Guillermo González Health Center, in order to design nursing actions based on the model of Dorothea Orem. It was worked with a descriptive, quantitative and cross-sectional study; for data collection, it was used a survey of own authorship based on the questionnaire of self-care activities in diabetes of the Universidad de los Andes of Colombia created by Daniel Parra, it has a content validity index of 0.96, composed by 16 questions evaluated using the Likert frequency scale, for its validity, pilot tests were applied to 15 people. The study sample consisted of 132 participants who met the inclusion criteria. The results showed that 65.91% of the respondents were female, and 47.73% were between the ages of 36 and 50. Regarding self-care activities, 73.49% mentioned that they sometimes follow a healthy diet, 42.42% always perform 30 minutes of daily physical activity, 42.67% always take the medication at the set time, and finally 67,42% always go to their medical checkups. Based on the results obtained, nursing actions were designed to strengthen the self-care of health, within which we have the interventions of: management of hyper and hypoglycemia, teaching in the process of disease and treatment, help with self-care and encouragement of exercise